2017
DOI: 10.1007/s10897-017-0132-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Counseling of Low‐Income Limited English Proficient Latina Women Using Medical Interpreters: Implications for Shared Decision‐Making

Abstract: In cancer genetic counseling (CGC), communication across language and culture challenges the model of practice based on shared decision-making. To date, little research has examined the decision-making process of low-income, limited English proficiency (LEP) patients in CGC. This study identified communication patterns in CGC sessions with this population and assessed how these patterns facilitate or inhibit the decision-making process during the sessions. We analyzed 24 audio recordings of CGC sessions conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 52 publications
2
47
4
Order By: Relevance
“…In observed CGC sessions that were part of the larger investigation of which our study is one part, Kamara and colleagues found that for low-income LEP Latina women undergoing CGC, adoption of such nontraditional roles by interpreters promoted better communication between patients and GCs and potential errors in interpretation were avoided (Kamara et al, 2018). They cite one instance of cultural brokering in which the interpreter was able to clarify for the patient that the documents the GC requested only involved documentation of income to facilitate subsidized testing and not, as the patient feared, immigration documents (Kamara et al, 2018).…”
Section: Parameters Of the Interpreter Rolementioning
confidence: 94%
See 1 more Smart Citation
“…In observed CGC sessions that were part of the larger investigation of which our study is one part, Kamara and colleagues found that for low-income LEP Latina women undergoing CGC, adoption of such nontraditional roles by interpreters promoted better communication between patients and GCs and potential errors in interpretation were avoided (Kamara et al, 2018). They cite one instance of cultural brokering in which the interpreter was able to clarify for the patient that the documents the GC requested only involved documentation of income to facilitate subsidized testing and not, as the patient feared, immigration documents (Kamara et al, 2018).…”
Section: Parameters Of the Interpreter Rolementioning
confidence: 94%
“…This exploratory study examined the perspectives of both GCs and HIs on CGC sessions conducted with remote (telephone or video) interpreters. This study emerged from clinical observations conducted for a study of CGC communication in two safety net hospitals in large metropolitan areas of California serving ethnically diverse patients, nearly all of whom have Medicaid and Medicare or are uninsured (Joseph et al, 2017) Those observations revealed an uneven quality of interpretation, and challenges for GCs working with LEP patients and interpreters (Cheng et al, 2018;Jacobs et al, 2005;Kamara, Weil, Youngblom, Guerra, & Joseph, 2018). Thus, our primary research questions were: what training and expertise do interpreters bring to the CGC encounter, what are their perspectives on the CGC encounter, and what types of challenges do HIs and GCs perceive in their respective roles and their partnered working relationship during interpretermediated CGC encounters?…”
Section: Introductionmentioning
confidence: 99%
“…It is well‐studied that interpreters do improve access to healthcare for patients with limited‐English proficiency in the United States, particularly with Spanish‐speaking populations, by bridging a gap that is created by a language barrier (Eamranond, Davis, Phillips, & Wee, ; Flores, ; Kamara, Weil, Youngblom, Guerra, & Joseph, ; Karliner, Jacobs, Chen, & Mutha, ; Schwei et al, ). However, a trained interpreter alone is not sufficient, as the provider must also communicate proficiently with the patient in this setting (Angelelli, ; Diamond & Jacobs, ; Hsieh, ).…”
Section: Introductionmentioning
confidence: 99%
“…Medical interpreters are needed to assist them in navigating the health‐care system. However, interpreters may not themselves understand the full complexity of the information counselors are attempting to communicate (Kamara et al, ), and in an attempt to simplify the counselor's words, misinterpretation can occur. Differences which may appear to be subtle to the interpreter may actually reflect a significant deviation from the counselor's intent (Browner et al, ; Joseph et al, ).…”
Section: Challenges and Opportunities For Genetic Counselorsmentioning
confidence: 99%
“…As a result, it is imperative that counselors are aware of this and subsequently ensure that they avoid the use of such words. Genetic counselors should also take time to employ teach‐back strategies and open‐ended questions to assess patient understanding (Kamara et al, ). Particular attention to contracting at the beginning of the session is critically important in these instances, as patients, who may be very unfamiliar with the patient‐focused approach of genetic counselors, may have distinctly different expectations of the interaction.…”
Section: Challenges and Opportunities For Genetic Counselorsmentioning
confidence: 99%